In-situ generation Cu2O/CuO core-shell heterostructure based on copper oxide nanowires with enhanced visible-light photocatalytic antibacterial activity. Issue 15 (1st August 2022) - Han, Lu; Zhan, Weiting; Liang, Xu; Zhang, Wei; Huang, Ruibin; Chen, Rongsheng; Ni, Hongwei
Abstract: As visible light-driven photocatalysts in wastewater treatment, Cu2 O/CuO composites have garnered considerable attention. Herein, Cu2 O/CuO core–shell nanowires were fabricated directly on a Cu mesh using a simple two-step synthesis process involving a wet chemical method and rapid annealing. Unlike conventional composite nanowires, controllable core–shell nanowires exhibit high photoelectrochemical properties and overcome the problems associated with the recovery of powder-based photocatalysts. The presence and structural distribution of the Cu2 O/CuO core–shell nanowires were confirmed using X-ray diffraction, X-ray photoelectron spectroscopy and transmission electron microscopy. Among the samples subjected to different rapid annealing temperatures for 180 s, the sample exposed to rapid annealing at 350 °C achieved the highest photocurrent density of −6.96 mA cm −2 . In the core–shell nanowires fabricated on the samples, the ratio of Cu2 O/CuO was 1:1. The photocatalytic activity of the Cu2 O/CuO nanowire samples was also determined by measuring methyl blue degradation to determine their applicability in wastewater treatment. A remarkable photocatalytic degradation rate of 91.6% was achieved at a loading bias voltage of −0.5 V. The Cu2 O/CuO heterojunction enhanced the photodegradation of the samples because the different bandgaps improved the dissociation of the photogenerated electron–hole pairs. Furthermore, the antibacterial activity of the Cu2 O/CuO nanowires exhibited considerable resistance against Escherichia coli and photocatalytic antibacterial treatment for only 20 min under visible light killed 10 6 CFU/mL of E. coli . Therefore, the Cu2 O/CuO controllable core–shell nanowires with a high photodegradation performance and excellent antibacterial activity under general illumination show diverse applications in water treatment.